Hubungan Konsumsi Makanan Sumber Lemak, Karbohidrat dan Aktivitas Fisik dengan Rasio Lingkar Pinggang Panggul (RLPP) pada Pengemudi Truk PO. Agm Kudus - Maila Try Haryati; Agustin Syamsianah; Erma Handarsari (Jurnal Gizi, 2013)
Fat deposits in the abdominal cavity that is known to be technically able to see thevalue of the waist circumference to hip circumference or better known as the waist -hip circumference ratio ( RLPP ). Waist hip circumference ratio values that reflect how many high fat deposits in the abdominal cavity. Consumption of fatty foods can increase hip and waist circumference weight. Decline in physical activity is also related to increased waist circumference. The general aim of this study is the relationship of food resource consumption of fats, carbohydrates and physical activity with waist belt circumference ratio ( RLPP ) at teamster PO AGM Kudus.  Type Explanatory research is research with cross- shopping approach ( crossectional ). Total sample of 30 teamsters PO. AGM. Not possible extraction of samples for all units studied population. Normality test data using the Kolmogorov-Smirnov test processed using a computer program SPSS version 18.0.  Test used is the Spearman Rank Test. The results showed that 53.3 % of respondents age 36-45 years, 56.7 % high school education/MA, 70 % fat consumption level more categories, 53.3 % carbohydrate consumption level of good category, 63.3 % physical activity categories are, and a 90 % ratio of waist circumference risk of hip degenerative disease category.   Conclusion that there is relationship between fat consumption level with waist hip circumference ratio ( p-value = 0,004 ), there was no relationship between the level of carbohydrate consumption with waist hip circumference ratio ( p-value = 0,326 ), and thereis no relationship between physical activity with the rate at Waist belt circumference ( p-value = 0,064 ). The teamster to eat a balanced diet, especially foods that contain energy and carbohydrate source, source of protein, fat source, and the source of other micronutrients needed enough. This is to support the teamster physical activity and prevent the risk of degenerative diseases.Key word : fat intake, carbohidrat intake, physical activity, waist circumference to hip circumference